Presentation and survival by hormonal receptor status in metaplastic breast cancer: A propensity score-matched analysis - Siqin Wang; Jin Hu; Yanting Zhang; Jian Shen; Fang Dong; Ximeng Zhang; Chong Lu; Dan Shang (Breast, 2021)
Background: Metaplastic breast cancer (MBC) is a rare and aggressive form of breast cancer. The effectiveness of chemotherapy (CT) for MBC remains controversial. The present study aimed to evaluate the efficacy of CT combined hormone receptor (HR) status on MBC patients with high risk (T1-4N2-3M0 and T4N0-1M0) by propensity-score matching (PSM). Methods: A retrospective study was performed to analyze MBC from the SEER database. Breast cancer-specific survival (BCSS) was analyzed using the Kaplan–Meier curve. Cox proportional hazard models were used to assess BCSS. PSM was used to make 1:1 case-control matching. Results: This study identified 3116 patients. The median follow-up time was 44 months (range, 1–321 months). About 62.5 % of patients received CT. 23.0 % of patients were HR-positive. Recurrence risk had a significant difference between the HR-negative and HR-positive groups. In the multivariable Cox regression model, CT had no benefit for MBC patients. HR status was not associated with a better prognosis. In subgroup analysis, the Kaplan–Meier analysis showed that HR-negative MBC with intermediate-risk benefited from CT. For HR-positive MBC, patients with intermediate and high risk also benefited from CT. After PSM, neither CT nor HR status was not related to better BCSS. Moreover, the use of CT could only improve the survival of HR-positive MBC patients with high risk. Conclusion: PSM analysis showed that HR status was not associated with a better prognosis. CT was not a significant prognostic factor for prognosis. However, HR-positive MBC patients with high risk might benefit from CT.